2023
DOI: 10.15252/emmm.202317393
|View full text |Cite
|
Sign up to set email alerts
|

Systemic gene therapy rescues retinal dysfunction and hearing loss in a model of Norrie disease

Valda Pauzuolyte,
Aara Patel,
James R Wawrzynski
et al.

Abstract: Deafness affects 5% of the world's population, yet there is a lack of treatments to prevent hearing loss due to genetic causes. Norrie disease is a recessive X‐linked disorder, caused by NDP gene mutation. It manifests as blindness at birth and progressive sensorineural hearing loss, leading to debilitating dual sensory deprivation. To develop a gene therapy, we used a Norrie disease mouse model (Ndptm1Wbrg), which recapitulates abnormal retinal vascularisation and progressive hearing loss. We delivered human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Our research group has demonstrated that a single intra-vitreal injection of Norrin protein can accelerate vascular regrowth and reduce inner-retina neuronal cell loss in the mouse oxygen-induced retinopathy model [6,45]. More recently, Pauzuolyte et al (2023) have shown that intravenous treatment of Ndp knockout mice with an adeno-associated viral vector 9 (AAV9) could rescue the failed development of the microvasculature in the neural retina and cochlea [46].…”
Section: Ndpmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has demonstrated that a single intra-vitreal injection of Norrin protein can accelerate vascular regrowth and reduce inner-retina neuronal cell loss in the mouse oxygen-induced retinopathy model [6,45]. More recently, Pauzuolyte et al (2023) have shown that intravenous treatment of Ndp knockout mice with an adeno-associated viral vector 9 (AAV9) could rescue the failed development of the microvasculature in the neural retina and cochlea [46].…”
Section: Ndpmentioning
confidence: 99%
“…nopathy model [6,45]. More recently, Pauzuolyte et al ( 2023) have shown that intravenous treatment of Ndp knockout mice with an adeno-associated viral vector 9 (AAV9) could rescue the failed development of the microvasculature in the neural retina and cochlea [46].…”
Section: Fzd4mentioning
confidence: 99%
“…Wang et al, 2012) and Frizzled-4 knockout mice experience vascular degeneration in these tissues as well as the inner ear (Xu et al, 2004). In fact, dysregulation of the canonical Wnt/β-catenin pathway is the cause of Norrie disease, a progressive vascular disorder that results in hearing loss (Bryant et al, 2022; Pauzuolyte et al, 2023; Rehm et al, 2002). Since we dissect the whole SV including all the components of the BLB for our in vitro cultures, it would be pertinent in future work to gain a molecular perspective on the vascular cells of the SV.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Inherited forms of deafness are highly prevalent and severe conditions that significantly affect 5% of the world’s population, the lack of therapeutic options for these conditions poses a major socioeconomic burden. [ 1 , 2 ] So far, many genetic factors have been found to cause deafness. However, there is a lack of treatments to prevent hearing loss due to genetic causes.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of treatments to prevent hearing loss due to genetic causes. [ 2 ] The discovery of new genetic pathogenic genes is particularly important for the prevention and treatment of deafness. A recent study found that THOC1 deficiency leads to late-onset nonsyndromic hearing loss in zebrafish, [ 3 ] but no case of deletion in THOC1 has been reported.…”
Section: Introductionmentioning
confidence: 99%